2007
DOI: 10.1007/s11244-007-0214-y
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of S-poisoned Pd/Al2O3 and Pd/CeO2/Al2O3 catalysts for the combustion of methane

Abstract: This work investigates the regeneration of S-poisoned Pd/Al 2 O 3 and Pd/CeO 2 /Al 2 O 3 catalysts under different CH 4 containing atmospheres. Under lean combustion conditions in the presence of excess O 2 , partial regeneration took place for both systems only above 750°C after decomposition of stable sulphate species adsorbed on the support. Under alternate lean combustion/CH 4 -reducing pulse regeneration is markedly anticipated down to 550-600°C. Experiments evidenced an effective role of ceria in prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
(41 reference statements)
1
6
0
Order By: Relevance
“…The most probable explanation is that sulfur species decompose in the neighborhood of the palladium particles more efficiently at higher temperatures and thus, after the 30 minutes treatment at higher temperatures only bulk Al2(SO4)3 exists. The gained results are in agreement with the results by Arosio et al [19]. Figure 10.…”
Section: Regenerated Catalystssupporting
confidence: 92%
See 2 more Smart Citations
“…The most probable explanation is that sulfur species decompose in the neighborhood of the palladium particles more efficiently at higher temperatures and thus, after the 30 minutes treatment at higher temperatures only bulk Al2(SO4)3 exists. The gained results are in agreement with the results by Arosio et al [19]. Figure 10.…”
Section: Regenerated Catalystssupporting
confidence: 92%
“…However, only a few scientific articles on the regeneration of sulfurpoisoned natural gas oxidation catalysts have been published. Arosio et al [19] have studied the regeneration of the sulfur-poisoned Pd/Al2O3 catalysts by short (2 minutes) CH4 pulses. Significant regeneration was observed already at 550 °C and almost complete reactivation of the catalyst was achieved at 600 °C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low sulfur content of the model catalyst gas was further supported by the absence of the asymmetric stretching vibration of sulfate group at 1150 cm -1 in the FTIR spectrum(Figure 5b). The residual sulfur present in the catalyst provides a reasonable explanation to the observation that methane conversion activity of a sulfur-poisoned Pd/Al2O3 catalyst cannot be fully recovered at realistic operation conditions[2,11,13,14,24,25]. However, the regeneration under simulated exhaust gas resulted in a significantly lower sulfur content of the model catalyst compared to the sulfur content obtained by regeneration under flowing H2 (Section 3.2.…”
mentioning
confidence: 73%
“…The deactivation of ceria-containing methane oxidation catalysts in presence of sulfur compounds is a common finding in the literature [125][126][127], both in absence and in presence of water co-fed in the reaction mixture. Nevertheless, it was also reported that a sulfated Pd/CeO2/Al2O3 catalyst can be reactivated at lower temperature following a CH4-reducing pulse compared to non-doped Pd/Al2O3, and this was attributed to the effect of ceria in preserving some PdO from sulfation [128,129], in agreement with the observation that the overall amount of SO2 adsorbed is lower on Pd/CeO2/Al2O3 compared to Pd/Al2O3 when sulfation is carried out under lean reaction conditions [122]. A decrease of the sulfates decomposition temperature in inert atmosphere is reported also when ceria or ceria-zirconia are added to Pd/Al2O3 catalyst [130].…”
Section: Poisoning and Deactivation Of Pd-based Catalystsmentioning
confidence: 99%